Effect of carbon black amounts on dynamic properties of natural rubber/trans-1,4-polyisoprene blends - WAN Lin, LI Xiang-yu, DONG Fu-wei, DU Ai-hua (Hecheng xiangjiao gongye)
A series of rubber samples with hardness gradient were prepared by blending natural rubber with trans-1,4-polyisoprene and adjusting the amount of carbon black N 330. The physical and mechanical properties and dynamic mechanical properties of the blended vulcanizates were studied. The results showed that the comprehensive physical and mechanical properties of the blend with a carbon black amount of 20 phr (by mass) were relatively excellent. The melting temperature of trans-1,4-polyisoprene in the blend was estimated to be around 47 ℃ through dynamic mechanical analysis. The test results of the electro-hydraulic servo material tester showed that the natural frequency of the blend increased with the increase of carbon black amount and decrease of vibration amplitude and static compression load, and the ratio of dynamic and static stiffness increased with the increase of carbon black amount and static compression load.